EFEKTIFITAS KOMBINASI TERAPI MUSIK DAN SLOW DEEP BREATHING TERHADAP PENURUNAN TEKANAN DARAH PADA PASIEN HIPERTENSI - T., Sebastianus K.; K., Tri Wulandari; Khoiriyati, Azizah (Universitas Muhammadiyah Yogyakarta, 2015)
Hypertension is an increasing of blood pressure that does not cause symptoms for many years until there is asigniicant organ damage and the cause of the increasing of morbidity and mortality in Indonesia. The combination of music therapy and slow deep breathing help controlling blood pressure gradually. This condition will maintain the patient to not experience complications. The purpose of this research is to determine the efects of music therapy combined with slow deep breathing to decrease blood pressure in patients with hypertension. This research is quasy-experiment with pretest- posttest control group design. Samples in this study are 56 respondents who are the patients with primary hypertension in Alak Public Health Centerwhich are divided into 28 people for treatment group and 28 people for control group by simple random sampling. The irst stage iscarrying out the measurements of blood pressure and giving intervention in the treatment group for 20 minutes, then measuring blood pressure. Meanwhile, the blood pressureof control group is measured. The second stage is 4 times monitoring visits in the group treated for 2 weeks and the post data in the control group at the end of the second week. The dataof average changes in per-post are analyzed using the Wilcoxon test and comparison of two groups using the Mann-Whitney test. The result shows the average change in blood pressure treatment group is higher than the control group. The statistic analysis of p value of systolic and diastolic blood pressure is0.05. There is a decrease in changes in systolic and diastolic blood pressure (p value = 0.000) of treatment group and the control group. It can be concluded that the combination of music therapy with slow deep breathing is efective in lowering the blood pressure of patients with primary hypertension and there is a change in blood pressure of treatment group and control group.Key words: Blood Pressure, Combination of music therapy and slow deep breathing, Hypertension